2015
DOI: 10.18632/oncotarget.3299
|View full text |Cite
|
Sign up to set email alerts
|

2D-DIGE proteomic analysis identifies new potential therapeutic targets for adrenocortical carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare aggressive tumor with poor prognosis when metastatic at diagnosis. The tumor biology is still mostly unclear, justifying the limited specificity and efficacy of the anti-cancer drugs currently available. This study reports the first proteomic analysis of ACC by using two-dimensional-differential-in-gel-electrophoresis (2D-DIGE) to evaluate a differential protein expression profile between adrenocortical carcinoma and normal adrenal. Mass spectrometry, associated with 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…The high rate of anabolic processes sustaining cancer cell proliferation and progression in a ROS-rich environment requires a high chaperone activity to ensure a correct protein folding process. Increased HSPs expression has been observed in various types of malignancies [46], including adrenocortical cancer [47]. In particular, HSP27, 60 and 70 play a pivotal role in dampening the apoptotic processes at mitochondrial level [45, 48], thus representing promising anti-tumor targets for the development of anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of anabolic processes sustaining cancer cell proliferation and progression in a ROS-rich environment requires a high chaperone activity to ensure a correct protein folding process. Increased HSPs expression has been observed in various types of malignancies [46], including adrenocortical cancer [47]. In particular, HSP27, 60 and 70 play a pivotal role in dampening the apoptotic processes at mitochondrial level [45, 48], thus representing promising anti-tumor targets for the development of anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings further suggest (see the study by Pinheiro et al mentioned earlier) that a metabolic shift toward aerobic glycolysis (Warburg effect) takes place in malignant ACT. More recently, another study confirmed that ACCs harbor significant changes in their glucose metabolic pathways and in addition identified fascin-1 as overexpressed in ACC compared to normal adrenal (Poli et al 2015). This protein has an important role in cytoskeletal organization and is associated with malignancy in a variety of cancers (Hashimoto et al 2011).…”
Section: Molecular Markers Reveal Disease Mechanisms and Improve Patimentioning
confidence: 87%
“…Poli et al reported a different proteomic profile in adrenocortical carcinoma compared with normal adrenal cortex characterized by overexpression of mainly metabolic enzymes that can be a potential target for novel therapeutics. [146]…”
Section: Discussionmentioning
confidence: 99%